Trace fossils on dinosaur bones reveal ecosystem dynamics along the coast of eastern North America during the latest Cretaceous - Brownstein,Chase D. (PeerJ, 2018)
Direct evidence of paleoecological processes is often rare when the fossil record is poor, as in the case of the Cretaceous of eastern North America. Here, I describe a femur and partial tibia shaft assignable to theropods from two Late Cretaceous sites in New Jersey. The former, identifiable as the femur of a large ornithomimosaur, bears several scores interpreted as shark feeding traces. The tibia shaft has punctures and flaked bone from the bites of mid-sized crocodyliforms, the first documented occurrence of crocodyliform traces on dinosaur bone from the Maastrichtian of the Atlantic Coastal Plain. The surface of the partial tibia is also littered with indentations interpreted as the traces of invertebrates, revealing a microcosm of biological interaction on the coastal seafloor of the Cretaceous Atlantic Ocean. Massive crocodyliforms, such as Deinosuchus rugosus and the slightly smaller Deltasuchus motherali, maintained the role of terrestrial vertebrate taphonomic process drivers in eastern North America during the Cretaceous. The report of crocodyliform bite marks on the ornithomimosaur tibia shaft in this manuscript reinforces the importance of the role of crocodyliforms in the modification of terrestrial vertebrate remains during the Cretaceous in North America. The preserved invertebrate traces add to the sparse record of the presence of barnacles and other marine invertebrates on dinosaur bone, and the evidence of shark feeding on the ornithomimosaur femur support the “bloat-and-float” model of terrestrial vertebrate fossil deposition in marine deposits from the Cretaceous of eastern North America.
Keywords: Taphonomy; Cretaceous; Dinosaurs; Appalachia; Theropods; Crocodyliforms